2010
DOI: 10.1016/j.ijantimicag.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for 2009 H1N1 influenza: evaluation of the published evidence

Abstract: ABSTRACT(85.0%) of 745 patients received antibiotics. Comparative data from the largest included study (involving 1088 patients) indicated that administration of antivirals within 2 days from symptom onset was significantly associated with reduced mortality (P < 0.001). In summary, the scarcity of comparative available data hampered the establishment of any firm conclusions regarding the benefit that various treatment strategies may confer to patients with 2009 H1N1 influenza. Studies with a comparative design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 22 publications
1
31
0
2
Order By: Relevance
“…No studies allow us to conclude when to suspend antiviral treatment in seriously ill patients, though in the Spanish ICUs the patients received a median of 10 days of treatment. 44,71,82,83,95 Recent studies have described much longer PCR positivity for the virus in critical patients, particularly in those with pneumonia. Ling et al 15 found the mean elimination time to be 6 days, though the virus was still detected in 37% of the patients by day 7, with no apparent relationship to early therapy.…”
Section: Which Antiviral Drug At What Dose and For How Long?mentioning
confidence: 99%
“…No studies allow us to conclude when to suspend antiviral treatment in seriously ill patients, though in the Spanish ICUs the patients received a median of 10 days of treatment. 44,71,82,83,95 Recent studies have described much longer PCR positivity for the virus in critical patients, particularly in those with pneumonia. Ling et al 15 found the mean elimination time to be 6 days, though the virus was still detected in 37% of the patients by day 7, with no apparent relationship to early therapy.…”
Section: Which Antiviral Drug At What Dose and For How Long?mentioning
confidence: 99%
“…Modulating the immune response post infection to control inflammation or pre-infection to provide increased protection for high risk groups has been a major theme in severe influenza infection research [10][11][12][13][14][15][16][17][18][19][20]. Corticosteroids have been suggested as a potential treatment option for patients undergoing severe IAV infection with accompanied cytokine storm [21][22][23][24][25], while pre-stimulating interferon-associated pathways have been suggested to protect high-risk groups [7,20,26,27].…”
Section: Immune Modulation For the Treatment Of Iav Infectionmentioning
confidence: 99%
“…Modulating inflammation during ongoing antiviral therapy to reduce resultant immunopathology should be beneficial and increase the chances for lower morbidity and mortality. However, the anti-inflammatory drugs currently on the market to combat influenza virus-induced inflammation, such as corticosteroids, have not been effective in improving disease outcome [64][65][66].…”
Section: S1p Receptor Signaling In Established Influenza Virus Infectmentioning
confidence: 99%